Harapan Pasien, Kompetensi Pegawai, Kualitas Pelayanan dan Kepuasan Pasien - Lia Noviana; A.A.N. Eddy Supriyadinata Gorda (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis study aims to fine out the effect of patient's expectation on the service quality, to find out the effect of the competence of employees on the service quality, to find ut the effect of patient expectations on patient satisfaction, to find out the effect of employee competence on patient satisfaction, to find out the effect of service quality on patient satisfaction in dental Polyclinic of Udayana hospital. The research was conducted at Dental Polyclinic of Udayana Hospital. The data were collected using questionnaires using differential scale semantics. The number of samples was used 100 people. Data analysis technique by using SEM. The results showed the higher expectation of the patient hence higher the service quality accepted with CR value of 10,181 and sig 0,000. The higher employee’s competence hence the higher the service quality accepted with CR 4,308 and sig 0,000. The higher patient’s expectation hence the higher patient’s satisfaction accepted with CR 2,679 and sig 0,000. The higher employee’s competence hence the higher the patient's satisfaction accepted with CR 2,183 and sig 0,045. The higher the service quality hence the higher the patient’s satisfaction accepted with CR value of 5,874 and sig 0,000.